Structural Analysis of the Impact of Regional Expenditures and Employment on Poverty Depth - Agustin, Fina Erviana; Bintoro, Nugroho Suryo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Indicators of government success in development can be seen from the low-income inequality and the depth of poverty. These goals can be achieved through budget realization for the public interest in the form of spending on education, health, and social protection functions. In addition to the government's role, other factors, such as the labor force participation rate and economic growth, also play an important role in reducing poverty. East Java Province occupies the region with the highest number of poor people in Indonesia with inequality showing an increasing trend. With this problem, this study used a sample of 38 districts/cities in East Java Province in 2018-2023 with the SEM-PLS method. The results show that economic growth, education function expenditure, and social protection function expenditure have a significant effect on poverty depth. In addition, economic growth and social protection function spending also have a significant effect on poverty depth through income inequality. Thus, there are indications that economic growth in East Java is less inclusive. The oversupply of labor and the inadequate quality of human resources fail to meet the needs of the labor market.